Changes in circulating cell-free DNA and nucleosomes in patients with exacerbated psoriasis - Beranek, Martin; Fiala, Zdenek; Kremlacek, Jan; Andrys, Ctirad; Krejsek, Jan; Hamakova, Kvetoslava; Chmelarova, Marcela; Palicka, Vladimir; Borska, Lenka (Archives of dermatological research, 2017)
Psoriasis is a multifactorial chronic inflammatory disease. We aimed to examine blood levels of nucleosomes derived from apoptotic cells, nucleosomal cell-free DNA (cfDNA) and immune-inflammatory biomarkers tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), and interleukin 6 (IL-6) in psoriatic subjects. The study included 28 patients with exacerbated psoriasis vulgaris and 22 controls. The clinical and laboratory investigations included the determination of PASI score, BMI, cfDNA (by real-time PCR), nucleosomes, TNF-α, CRP, and IL-6. The range of PASI score in psoriatic patients was 10-34 (median 19). In the patients, we found significantly elevated levels (p < 0.001) of cfDNA, nucleosomes, TNF-α, CRP, and IL-6. We did not find any significant relationship between the analyzed parameters in either group (i.e., experimental or control). Elevated levels of the biomarkers of inflammation (TNF-α, CRP, and IL-6) and the indicators of apoptosis (cfDNA, circulating nucleosomes) proved that exacerbated psoriasis vulgaris is associated with a high degree of systemic inflammatory responses and dysregulated apoptotic pathways.
Keywords: Young Adult; Male; biologické markery; Inflammation; Tumor Necrosis Factor-alpha; psoriáza; progrese nemoci; mladý dospělý; Biomarkers; Cell-free DNA; Interleukin-6; Adult; C-reaktivní protein; Aged; dospělí; mužské pohlaví; senioři; Disease Progression; nukleozomy; Severity of Illness Index; zánět; Nucleosomes; lidé; Psoriasis; ženské pohlaví; interleukin-6; Humans; volné cirkulující nukleové kyseliny; apoptóza; TNF-alfa; Cell-Free Nucleic Acids; C-Reactive Protein; stupeň závažnosti nemoci; Female; lidé středního věku; Apoptosis; Middle Aged